(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Aahara (Food) is considered as the first pillar among three Nidra and Abrahmacharya being other two. Many common health problems can be prevented through nutritious diet Nutritional disorders are described in scattered manner in Ayurveda texts. Balshosha is disease a similar to undernutrition. In Ayurveda disease such as Parigarbhika, Phakka, Balashosha, and Shuska Revati are similar to Balshosha. Childhood undernutrition is an underlying cause in an estimated 35% of all deaths among children under five and 21% of total global disability adjusted life years lost among less than 5 children. Food is important as a nutritional source, also with therapeutic value and most importantly it plays a vital role during the post treatment period in re-gaining the diminished strength due to the harmful effect of the disease. Nutritional disorders are described in scattered manner in Ayurveda texts. Childhood undernutrition is an underlying cause in an estimated 35% of all deaths among children under five and 21% of total global disability adjusted life years lost among less than 5 children.